On uniqueness theorems for holomorphic curves sharing hypersurfaces without counting multiplicity - Phuong Ha Tran (Український математичний журнал, 2011)
We prove some uniqueness theorems for algebraically nondegenerate holomorphic curves sharing hyper-surfaces ignoring multiplicity.